Nonlinear modelling of autoregressive structural breaks in a US diffusion index dataset - George Kapetanios; Elias Tzavalis (Queen Mary University of London, Department of Economics, 2005)
This paper applies a new model of structural breaks developed by Kapetanios and Tzavalis (2004) to investigate if there exist structural changes in the mean reversion parameter of US macroeconomic series. Ignoring such type of breaks may lead to spurious evidence of unit roots in the autoregressive parameters of economic series. Our model specifies that both the timing and size of breaks are stochastic. We apply the model to a variety of macroeconomic and finance series from the US.
Keywords: E32; C13; C22; 330; Structural breaks; State space model; Nonlinearity; Strukturbruch; Sch\~AƒÂtzung; USA; Zustandsraummodell; Nichtlineares Verfahren